(untitled) (Innovative professional education, 2023)
Learners like visual content more than text because it can be more interesting and understandable. Educational infographics can be visually rich, contain images, or have hyperlinks that make the learning process more engaging and engaging for learners. Additionally, infographics can be more understandable to learners if they are adapted for different levels of learning ability.